Hypofractionated carbon ion therapy delivered with scanned ion beams for patients with hepatocellular carcinoma - Feasibility and clinical response - Habermehl, Daniel; Debus, Juergen; Ganten, Tom; Ganten, Maria-Katharina; Bauer, Julia; Brecht, Ingo C.; Brons, Stephan; Haberer, Thomas; Haertig, Martin; Jaekel, Oliver; Parodi, Katia; Welzel, Thomas; et al. (Radiation Oncology, 2013)
Purpose: Photon-based radiation therapy does currently not play a major role as local ablative treatment for hepatocellular carcinoma (HCC). Carbon ions offer distinct physical and biological advantages. Due to their inverted dose profile and the high local dose deposition within the Bragg peak, precise dose application and sparing of normal tissue is possible. Furthermore, carbon ions have an increased relative biological effectiveness (RBE) compared to photons. Methods and materials: A total of six patients with one or more HCC-lesions were treated with carbon ions delivered by the raster-scanning technique according to our clinical trial protocol. Diagnosis of HCC was confirmed by histology or two different imaging modalities (CT and MRI) according to the AASLD-guidelines. Applied fractionation scheme was 4 × 10 Gy(RBE). Correct dose application was controlled by in-vivo PET measurement of β + -activity in the irradiated tissue shortly after treatment. Results: Patients were observed for a median time period of 11.0 months (range, 3.4-12.7 months). Imaging studies showed a partial response in 4/7 lesions and a stable disease in 3/7 lesions in follow-up CT- and MRI scans. Local control was 100%. One patient with multifocal intrahepatic disease underwent liver transplantation 3 months after carbon ion therapy. During radiotherapy and the follow-up period no severe adverse events have occurred. Conclusions: We report the first clinical results of patients with HCC undergoing carbon ion therapy using the rasterscanning technique at our institution. All patients are locally controlled and experienced no higher toxicities in a short follow-up period. Further patients will be included in our prospective Phase-I clinical trial PROMETHEUS-01 (NCT01167374).
CRIS-Team Scopus Importer:2023-03-08